“Vulneración del Derecho de Imparcialidad en el papel de la SUPERCOM en el Juzgamiento y Sanción a los Medios de Comunicación - Salinas Valverde, Henrry Modesto (2017)
Communication is an important step in the consolidation of the human being as a social factor, the media plays a significant role in the democratic life of a country, exercising power to influence public opinion. The 2013 communication law creates the Superintendency of Information and Communication for trial and punishment to the media Such is the case until April 2016 the Superintendency of information and communication to known and has sanctioned media recorded a total of 1538 sanctions manifested in attacks against freedom of expression mainly showing an exaggerated use of force , physical and verbal aggression, withdrawal and seizure of communications equipment, abuses of private property, closing, closing censorship and cancellation of programs, reversal frequency, resulting result in layoffs of workers made leaving unemployment these without have the means to survive generating violation of rights recognized by the Constitution as the right to work, inviolability of the home and of course Impartiality law. The Superintendency of information and communication to be judge and jury in the trial of the offenses referred to in the Communications Law violates the right of fairness and due process in determining liability and penalties to the media. 5 It is the duty of public orders protectively State, the effective protection of the rights and enforces the legal framework without distinction of persons or groups. Which is why I developed this research aimed to present a reform proposal that these rights are not violated?